Enhancing the Performance of Porous Concrete by Utilizing the Pumice Aggregate. (2015) - Hariyadi; Tamai, Hiroki
Abstract: High porosity, low modulus of elasticity, and adequate strength are the main requirements of the concrete structures as an impact energy absorber. The development of porous concrete mainly focuses on increasing the porosity rather than the strength due to many advantages can be gained when having higher porosity. Consideration to the environmental problem has been a concern recently, therefore utilization of a waste material as construction materials has been spreading widely. Volcanic pumice as one of waste materials having a high porosity can possibly be utilized as an aggregate replacement material on porous concrete to improve its porosity without much reducing the strength. The purpose of this research is to evaluate the effect of varying proportion of volcanic pumice as an aggregate replacement (VP/A) and proportion of aggregate to cement (A/C) with a constant water to cement ratio (WCR) to the mechanical properties of volcanic pumice porous concrete, and to those porous concrete with normal aggregate as a control. The result shows that by using volcanic pumice the porosity increases and the modulus of elasticity decreases, even though slightly decreasing in strength is also found. However, it showed a possibility of volcanic pumice porous concrete as impact energy absorber structures. This research is a preliminary study which is expected to be developed for future research related to the dynamic and impact test. In addition, ACI 318-08 developed equation (Ec = 0.043W 1.5 f'c 0.5 ) can be used to rapidly estimate the modulus of elasticity of porous concrete, where it is necessary, due to experimental difficulties to measure it.